2017
DOI: 10.1016/j.bj.2017.05.003
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the root and canal systems of maxillary molars in Taiwanese patients: A cone beam computed tomography study

Abstract: BackgroundThis study evaluated variations in root canal configuration in the maxillary permanent molars of Taiwanese patients by analyzing patients' cone beam computed tomography (CBCT) images. Comparisons were made among these configurations and those previously reported. This information may serve as a basis for improving the success rate of endodontic treatment.MethodsThe root canal systems of 114 Taiwanese patients with bilateral maxillary first or second molars were examined using CBCT images. The number … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 39 publications
2
26
0
Order By: Relevance
“…13,17,18,19 However, some authors showed that more than half of first maxillary molars had an MB2 root canal. 1,5,6,7,11,15,20,21,22,23,24,25 It was also observed that 23% of second molars had more than one root canal in the mesiobuccal root, a result similar to that found in other populations. 20,22,24 In several previous studies, MB2 canal frequency was from 29.4% to 57.93% in the maxillary second molars.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…13,17,18,19 However, some authors showed that more than half of first maxillary molars had an MB2 root canal. 1,5,6,7,11,15,20,21,22,23,24,25 It was also observed that 23% of second molars had more than one root canal in the mesiobuccal root, a result similar to that found in other populations. 20,22,24 In several previous studies, MB2 canal frequency was from 29.4% to 57.93% in the maxillary second molars.…”
Section: Discussionsupporting
confidence: 71%
“…1,5,6,7,11,15,20,21,22,23,24,25 It was also observed that 23% of second molars had more than one root canal in the mesiobuccal root, a result similar to that found in other populations. 20,22,24 In several previous studies, MB2 canal frequency was from 29.4% to 57.93% in the maxillary second molars. 1,6,7,13 In contrast, in the studies of Ghoncheh et al 15 and Lin et al, 24 only 13.84% and 7.7% of maxillary second molars presented a second canal in the mesiobuccal root, respectively.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…11,12 These methods include polyester resin impressions, creating transparent samples and taking radiographs in the mesiodistal and/or buccolingual directions. 13 Currently the main method that gives detailed information about the morphology of roots and their variations is CBCT.…”
Section: Cone Beam Computed Tomography (Cbct)mentioning
confidence: 99%
“…It is well-known that root and especially canal morphology differ greatly between populations, within populations and even within the same individuals [3,33]. Therefore, variations in the shape and number of root canals in populations appear to be genetically determined [24]. In endodontics, a lack of comprehensive knowledge about the anatomy of root canal systems might contribute to treatment failure.…”
Section: A B C D E Fmentioning
confidence: 99%